THE CHURCH TRANSPLANTED TO AMERICA. TWO HISTORIOGRAPHIC DEBATES. - Saranyana Closa, Josep-Ignasi (Imago Temporis. Medium Aevum, 2025)
Over the last hundred years, five great historiographic debates have attempted to explain the rapid acceptance of the Christian faith in Mesoamerica and also in the Inca epoch. Of these five debates, two are studied, analysed and are subjected to criticism here: 1) whether the first Franciscan evangelisation in the central valleys of New Spain was encouraged by "Joachimite" ideal; and 2) if a new spirituality penetrated New Spain, hand in hand with the writings of Erasmus, which would have facilitated the approach of the indigenous peoples to the Catholic faith and would have been a spiritual relaxation for the Spaniards transplanted to America, especially to Tierra Firme, in the first half of the sixteenth century.